THE EFFECT OF SPORTS HEALTH TREATMENT ON REDUCING THE PREVALENCE OF HYPERTENSION - Xiao,Li (2021)
ABSTRACT Introduction Hypertension is a common clinical disease, which is not uncommon in the aviation industry. Pilots suffering from high blood pressure need to control high blood pressure to ensure flight safety. Exercise therapy is an effective way to control high blood pressure. Objective To design the clinical effects of exercise intervention in the treatment of hypertension in pilots. Method The article randomly assigned 41 pilot volunteers with hypertension to two groups: the treatment and control groups. Except for the different exercise intervention therapy, the other treatment methods are the same. After the expiration of the experiment, the volunteers were tested for their physiological and biochemical indicators. Results After one year of strict diet and exercise intervention, the two groups of physiological and biochemical indicators were significantly different. Conclusion Intervention of moderate-intensity exercise can reduce the body mass index, waist-to-hip ratio and blood pressure level of hypertensive patients, correct the disorder of blood lipid metabolism, and can help reduce the recurrence rate of hypertension. Level of evidence II; Therapeutic studies - investigation of treatment results.